CONTRIBUTIONS OF SELECTED NON-TIMBER FOREST PRODUCTS TO COMMUNITY LIVELIHOODS IN TARABA STATE, NIGERIA (2017)
Non-Timber Forest Products (NTFPs) have been identified to contribute to community livelihoods. Such contributions are people as well as site specific and may be short-lived if continuous availability cannot be guaranteed. Information on the role of NTFPs in community livelihoods is crucial to their sustainable management; however, this role has not been properly documented in Taraba State. Therefore, contributions of selected NTFPs to community livelihoods in Taraba State were investigated. A four-stage sampling procedure was used in the study. Three Local Government Areas (LGAs) were randomly selected from each of the three existing Agro-ecological zones (AEZs) in Taraba State. Five wards from each LGA and 30 household heads (HHHs), using 30% sampling intensity were then randomly selected to give a total of 1,350 HHHs. Five sets of questionnaire were administered to 435 Harvesters, 188 Livestock Managers (LMs), 338 Marketers, 327 Building and Energy materials Suppliers (BEMSr) and 62 Medicinal Herbs Collectors (MHCs). The NTFPs were identified and prioritised. Contributions of selected NTFPs to community livelihoods were evaluated using Food, Livestock Feed (LF), Income and Employment Generation (IEG), Building and Energy Material Supplies (BEMS) and Medicinal Herbs Utilisation (MHU) as indices of livelihoods. Data were analysed using descriptive statistics, t-test, Chi-square and logistic regression at α0.05. Two hundred and six NTFPs were identified. Ten species having priority for community livelihoods were Afzelia africana (35), Balanites aegyptiaca (34.5), Vitellaria paradoxa (34), Parkia biglobosa (33.5), Irvingia gabonensis (33), Xylopia aethiopica (32.5), Faidherbia albida (32), Adansonia digitata (32), Brachystegia eurycoma (32), and Elaeis guineensis (31.5). Forty-six species of NTFPs were used as Food (36 trees, 3 shrubs, 7 herbs), twenty-four as BEMSr (17 trees, 3 shrubs, 4 herbs) and twenty-nine for MHU (24 trees, 2 shrubs, 3 herbs). The two hundred and six NTFPs belong to forty-four families. The NTFPs contributed N2,065±1197.43 to Harvesters, N1,523.18±977.71 to LMs, N4, 882.06±3391.75 to Marketers, N1, 268.47±2023.61 to BEMSr and N1, 553.23±1062.74 to MHU as income/month. The NTFPs contributions to community livelihoods were: 34.1% (food) 14.9% (LF); 22.9% (IEG); 22.8% (BEMS) and 5.3% (MHU). Community livelihoods significantly depended on NTFPs (χ2 = 94.83). Harvesters’ occupation (6.25), age (9.22), monthly income (2.13), AEZ (1.77), sex (1.65), educational status (1.22) and main forest based activities (1.21) are likely to influence their dependence on NTFPs for livelihood. The AEZs (6.88), sex (5.85) and age (4.09) of LMs are likely to influence their dependence on NTFPs, while monthly income (7.99), AEZ (6.28), sex (2.01) and educational status (1.63) of marketers are likely to influence their dependence on NTFPs for livelihood. Also, AEZ (1.98) and monthly income (1.31) are likely to influence BEMS dependence on NTFPs, while age (4.87), sex (6.84) and AEZ (4.29) are likely to influence MHC dependence on NTFPs for livelihood. Ten of the identified 206 Non-Timber Forest Products significantly enhanced livelihood status in Taraba State. These species are however under pressure due to multiple usage, which have implication for their sustainable management. In situ conservation is therefore recommended to mitigate the pressure on them